2022
DOI: 10.1093/oncolo/oyac081
|View full text |Cite
|
Sign up to set email alerts
|

Breast Nurse Intervention to Improve Adherence to Endocrine Therapy Among Breast Cancer Patients in South Ethiopia

Abstract: Introduction Many women in rural Ethiopia do not receive adjuvant therapy following breast cancer surgery despite the majority being diagnosed with estrogen-receptor-positive breast cancer and tamoxifen being available in the country. We aimed to compare a breast nurse intervention to improve adherence to tamoxifen therapy for breast cancer patients. Methods and Materials The 8 hospitals were randomized to intervention and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Sample sizes ranged from 26 to 250. Overall, eight studies reported operational definitions of medication adherence before assessment or measurement, 47 - 54 whereas five did not. 55 - 59 Eleven studies (85%) evaluated endocrine medications, one evaluated cytotoxic chemotherapies, 52 and one evaluated combined medications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sample sizes ranged from 26 to 250. Overall, eight studies reported operational definitions of medication adherence before assessment or measurement, 47 - 54 whereas five did not. 55 - 59 Eleven studies (85%) evaluated endocrine medications, one evaluated cytotoxic chemotherapies, 52 and one evaluated combined medications.…”
Section: Resultsmentioning
confidence: 99%
“…One randomized controlled trial (RCT) evaluated adherence-enhancing interventions. 47 The barriers and facilitators of OAM adherence and measurements are given in the Data Supplement. Five studies reported barriers only, 49 , 51 - 54 one reported facilitators only, 56 and four reported both barriers and facilitators.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows utilization of a cost-effective treatment with very little side-effects that can be administered even at primary or secondary level health facilities. A study from Ethiopia proved that a strategy involving the specialized training of "cancer nurses" to support patients during their 5 year treatment can improve adherence [37].…”
Section: Discussionmentioning
confidence: 99%
“…The study by Getachew et al examines the use of a multi-pronged nurse-led intervention to improve adherence to endocrine therapy in Ethiopia. 9 While the concept of oral medication adherence may appear simple, it encompasses multiple components (see Fig. 1 ).…”
mentioning
confidence: 99%